Influences of Ocean Currents on the Diets of Demersal Fish Communities in the Western North Pacific Revealed by Their Muscle Carbon and Nitrogen Isotopic Compositions - Ishikawa, Naoto F.; Ogawa, Nanako O.; Chikaraishi, Yoshito; Yamaguchi, Moto-omi; Fujikura, Katsunori; Miyairi, Yosuke; Yokoyama, Yusuke; Nagata, Toshi; Ohkouchi, Naohiko (Frontiers in Marine Science, 2021)
To study the influence of different ocean currents on the trophic spectra found in a sympatric fish community, we analyzed the radiocarbon contents (Δ14C) and stable carbon (δ13C) and nitrogen (δ15N) isotopic compositions in their bulk tissues and the δ15N of individual amino acids in 26 species of demersal fish collected from off Tohoku (Pacific coast), northeastern Japan. The Δ14C values of the fish varied from –42‰ to +41‰, consistent with the Δ14C of the dissolved inorganic carbon in the cold Oyashio Current (typically about –50‰) and the warm Kuroshio Current (typically about +50‰). The trophic positions of the fish estimated from the δ15N values of amino acids increased from 3.1 to 4.5 with increasing snout length. A negative correlation was observed between Δ14C and trophic position (TP) in gadiform fish and flatfish, suggesting that the Oyashio Current delivers a high TP diet to these fish groups. These results suggest that the trophic ecology of marine fish in the coastal western North Pacific is primarily controlled by the two major surface water currents, but is also significantly influenced by a combination of species-specific feeding and migration strategies.